2017
DOI: 10.1155/2017/2181942
|View full text |Cite
|
Sign up to set email alerts
|

Benign Effect of Extremely Low‐Frequency Electromagnetic Field on Brain Plasticity Assessed by Nitric Oxide Metabolism during Poststroke Rehabilitation

Abstract: Nitric oxide (NO) is one of the most important signal molecules, involved in both physiological and pathological processes. As a neurotransmitter in the central nervous system, NO regulates cerebral blood flow, neurogenesis, and synaptic plasticity. The aim of our study was to investigate the effect of the extremely low-frequency electromagnetic field (ELF-EMF) on generation and metabolism of NO, as a neurotransmitter, in the rehabilitation of poststroke patients. Forty-eight patients were divided into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 53 publications
5
48
0
Order By: Relevance
“…After a four-week rehabilitation program where one group also received ELF-EMF field (40 Hz, 7 mT for 15 min/day for four weeks), ELF-EMF induced a significant improvement in functional (Activities of Daily Living) and mental (Mini-Mental State Examination and Geriatric Depression Scale) status. As well as an increase in antioxidant gene expression, nitric oxide metabolites, oxidative stress, and interleukin-1β were all improved/increased [37][38][39][40][41][42]. Indeed, a neuroprotective role of IL-1β-dependent in the regulation of neurotrophic factors has already been hypothesized [43].…”
Section: Discussionmentioning
confidence: 95%
“…After a four-week rehabilitation program where one group also received ELF-EMF field (40 Hz, 7 mT for 15 min/day for four weeks), ELF-EMF induced a significant improvement in functional (Activities of Daily Living) and mental (Mini-Mental State Examination and Geriatric Depression Scale) status. As well as an increase in antioxidant gene expression, nitric oxide metabolites, oxidative stress, and interleukin-1β were all improved/increased [37][38][39][40][41][42]. Indeed, a neuroprotective role of IL-1β-dependent in the regulation of neurotrophic factors has already been hypothesized [43].…”
Section: Discussionmentioning
confidence: 95%
“…This fact has no implications on astrocyte culture, but at the nervous system level it could have a potentially effect on neurons. Nitric oxide (NO) is one of the most important signal molecules, involved in both physiological and pathological processes [11]. As a neurotransmitter in the central nervous system, NO regulates cerebral blood flow, neurogenesis, and synaptic plasticity.…”
Section: Fig 2 Standard Nano2 Curvementioning
confidence: 99%
“…As a neurotransmitter in the central nervous system, NO regulates cerebral blood flow, neurogenesis, and synaptic plasticity. Cichon and col. showed that application of extremely low frequency EMF significantly increased 3-nitrotyrosine and nitrate/nitrite levels, while expression of NOS 2 was insignificantly decreased in both groups, with improving in functional and mental status and promoting recovery in poststroke patients [11]. There are also strong evidences about the role of oxidative stress in neurological degeneration and glaucoma [12][13][14][15].…”
Section: Fig 2 Standard Nano2 Curvementioning
confidence: 99%
“…In paper [7], the processes of interaction between electromagnetic radiation, a biological object and a technical system were outlined. A biological object is represented by a homogeneous structure.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%